Russia and the USA Participation in the Group of Eight Activity - A G Savoyskiy (Vestnik RUDN. International Relations, 2011)
The article focuses on history of creation and meetings at the highest levels of leaders of industrially developed democratic countries of the world, since 1975 till 2010. The mechanism of summits' functioning, the activity of the Russian and American parties in summits for the further development of bilateral and multilateral interstate relations have been researched.